Model Praktik Lembaga Keuangan Mikro Syariah dalam Pemberdayaan UMKM di Masa Pandemi Covid-19 - Hidayat, Agus (Prodi Ekonomi Syariah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2021)
Micro, Small and Medium Enterprises (MSMEs) are components of business actors that play a significant role in improving the national economy, both in terms of gross domestic product, employment, or investment. This study aims to analyze the practice model of Islamic Microfinance Institutions in Empowering MSMEs in Indonesia. Analytical descriptive is used to describe the model. The findings of this study explain that the performance of microfinance for strengthening MSMEs has been good. From the aspect of capital, LKMS has been able to increase capital for MSMEs, so that the quantity of MSMEs production increases. There are several micro-financing models for strengthening MSMEs that may be applied by Islamic financial institutions, namely the solidarity group model, the village banking model, the grameen model, and the individual model.